Table of contents, editorial board, and other front matter - Hal R. Taylor (Journal of Applied Communications, 1981)
Editorial front matter and table of contents for vol.64, no.4, Oct-Dec (1981) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education